Mitigation of Power Oscillations Due to Variable Load and Plug-in Electric Vehicle by Multi-Objective STATCOM Controller Action - Satapathy, Samarjeet; Nahak, Narayan; Agrawal, Ramachandra; Mishra, Alok Kumar; Jena, Tarakanta; Patra, Akshaya Kumar (2025 International Conference in Advances in Power, Signal, and Information Technology (APSIT), 2025)
Damping of power system oscillation by fractional order PID (FOPID) controller based on STATCOM has been proposed in the present work. Multi machine system with the disturbances like variation in reference voltage and load change have been considered in step and discrete manner to validate the effectiveness of controller. A multi objective modified PSO optimization being proposed to tune FOPID controller. The change in speed has been studied with respective generators and performance of the proposed control actions have been compared with fractional PSO (FPSO) and with PSO optimized control action and it has been observed that the damping action of presented controller is superior in comparison to the PID based STATCOM controller and proposed modification in PSO performs better than conventional PSO algorithm. The experimentations done in this work are reference voltage, plug in electric vehicle (PEV) and load change for validating the effectiveness of control action with eigen distribution analysis in time domain. PID controller based on STATCOM control action and the modified PSO was compared with PSO and FPSO optimizations.